Implementasi Kurikulum Merdeka Dalam Pembelajaran Ilmu Pendidikan Islam Di Sekolah - Widodo, Antok; El-Yunusi , Muhammad Yusron Maulana (LP2M Universitas Islam Ahmad Dahlan, 2023)
Abstract Learning of the Islamic education often looks monotonous for students. This is due to several factors such as a lack of innovation from teachers, lagging behind in terms of digitalization, and a lack of ability to adapt their teaching styles to current developments. In addition, the current curriculum is independent learning, where students have the freedom to determine their learning interests. This research aims to find out how the independent curriculum is implemented in learning Islamic education in schools. In planning, implementing and evaluating PAI studies in the independent learning curriculum in schools, this research used qualitative descriptive methods. From the results and discussion it can be concluded that the independent curriculum focuses on developing the character and morals of students. The implementation of the independent curriculum is flexible, thereby giving the freedom to Islamic religious education teachers to develop learning. To achieving these goals, learning outcomes (CP), learning objective flow (ATP), standard documents, learning outcome indicators, and the time required must be determined based on students' learning interests so that students are expected to have maximum learning opportunities and valuable experiences.